Shear mechanical responses of sandstone exposed to high temperature under constant normal stiffness boundary conditions - Yin, Qian; Wu, Jiangyu; Zhu, Chun; He, Manchao; Meng, Qingxiang; Jing, Hongwen (Geomechanics and geophysics for geo-energy and geo-resources., 2021)
Characterizing the temperature-dependent shear mechanical responses of rock masses under constant normal stiffness (CNS) boundary conditions is of crucial importance for evaluating the stability and performance of deep underground projects. This paper experimentally analysed the shear mechanical properties and dilatancy deformation of sandstone exposed to high temperature with respect to various initial normal stresses under a constant normal stiffness. The results indicate that the developed thermally induced defects cause the porosity of sandstone to increase by 42.48% in a temperature range of 25–800 °C, while the P-wave velocity, unit weight and fractal dimension of pores are reduced. A typical shear failure process including a fracture surface generation process and a shear slipping process of surface asperities is identified. Due to the formation of fracture surfaces, both the normal displacement and normal stress curves show notable sudden drops. The peak shear strength, residual shear strength and terminal normal stress all display an exponential variation with temperature, i.e., initial fluctuations or a slight increase, then a dramatic decrease, achieving a threshold temperature of 400 °C. The secant peak shear stiffness declines by 43.79–70.48% in a temperature range of 400–800 °C due to enhanced ductility and decreasing peak shear strength. With increasing initial normal stress, both shear strength and terminal normal stress increase, but the terminal normal displacement decreases by 52.68–57.37% due to weakened dilation effects. The normal stress–shear stress variation paths are plotted, and the apparent internal friction angle decreases with temperature. Two representative failure patterns, including shear off of surface asperities and edge spalling of the rock matrix, are identified. Both the shear area and mass loss ratios of the sheared rock samples increase with both temperature and initial normal stress due to weakened shear strength and strong shear dilation inhibition effects. Article Highlights Temperature-dependent shear properties of sandstone under CNS conditions. Identifying a typical shear failure process of intact sandstone samples. Evaluating the dilatancy deformation with various initial normal stresses.